2015
DOI: 10.1186/s12864-015-2229-2
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome annotation and comparative genomic analyses of bio-control fungus Purpureocillium lilacinum

Abstract: BackgroundThe fungus Purpureocillium lilacinum is widely known as a biological control agent against plant parasitic nematodes. This research article consists of genomic annotation of the first draft of whole genome sequence of P. lilacinum. The study aims to decipher the putative genetic components of the fungus involved in nematode pathogenesis by performing comparative genomic analysis with nine closely related fungal species in Hypocreales.Resultsde novo genomic assembly was done and a total of 301 scaffol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 52 publications
0
33
0
1
Order By: Relevance
“…In addition, a previous study from rocks in the Atacama Desert reported the presence of some pathogenic Aspergillus species [19]. We also detected contigs related to Purpureocillium lilacinum, a species of filamentous fungus from the family Ophiocordycipitaceae (class Sordariomycetes) that has been isolated from deserts and which has demonstrated good potential as a biocontrol agent [26].…”
Section: Fungi As Endolithobionts Of Halitesmentioning
confidence: 56%
“…In addition, a previous study from rocks in the Atacama Desert reported the presence of some pathogenic Aspergillus species [19]. We also detected contigs related to Purpureocillium lilacinum, a species of filamentous fungus from the family Ophiocordycipitaceae (class Sordariomycetes) that has been isolated from deserts and which has demonstrated good potential as a biocontrol agent [26].…”
Section: Fungi As Endolithobionts Of Halitesmentioning
confidence: 56%
“…Endobacteria present between two layers of the envelope may produce and secrete enzymes essential for adhesion to or the penetration of the nematode’s body wall, which comprises substances between the two layers of the envelope of a mature lunate spore. The harbored endobacteria make E. vermicola very different from other nematophagous fungi ( 22 , 24 , 26 , 30 , 41 , 57 ), and this may result in a distinctive nematophagous mechanism for E. vermicola . Therefore, endobacteria may play prominent roles in shaping the formation of lunate spores, which influences nematocidal function, thereby contributing to further ecological success.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these species have been developed for commercially available products including Hirsutella minnesotensis, Pochonia chlamydosporia and Purpureocillium lilacinum [49]. All three of these species are natural inhabitants of soil environments and genome sequence data exists for representative isolates [50][51][52][53].…”
Section: Nematode Pathogensmentioning
confidence: 98%